2013
DOI: 10.2320/matertrans.mf201307
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features of the Extraordinary Low Glass Transition Temperature for Au<sub>65</sub>Cu<sub>18</sub>Si<sub>17</sub> Bulk Metallic Glass

Abstract: Au 65 Cu 18 Si 17 bulk metallic glass (BMG) exhibits an extraordinary low glass transition temperature (<100°C) and a wide supercooled liquid region. In order to elucidate the structural features of the extraordinary low glass transition temperature and high glass forming ability of the Au 65 Cu 18 Si 17 BMG, high-energy X-ray diffraction (HEXRD) and Extended X-ray Absorption Fine Structure (EXAFS) measurements were carried out using synchrotron radiation. A sharp first peak and oscillation of the structure fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…At around 5Å, a splitting of the second G(r) peak is observed. This splitting has also been observed in a similar Au 65 Cu 18 Si 17 BMG alloy [37]. The positions of the two subpeaks R 21 and R 22 were determined by fitting with a sum of two Gaussians (see right inset in Fig.…”
Section: High-intensity X-ray Scatteringsupporting
confidence: 65%
See 1 more Smart Citation
“…At around 5Å, a splitting of the second G(r) peak is observed. This splitting has also been observed in a similar Au 65 Cu 18 Si 17 BMG alloy [37]. The positions of the two subpeaks R 21 and R 22 were determined by fitting with a sum of two Gaussians (see right inset in Fig.…”
Section: High-intensity X-ray Scatteringsupporting
confidence: 65%
“…(5); namely, the reduced height of the first structure factor maximum S(Q 1 )/S[Q 1 (T 0 )] and the reduced FWHM w/w(T 0 ). Other studies on BMG systems have shown these quantities to be useful as complementary metrics to the peak position [37,55,57]. In a single-component system, the FWHM can characterize the degree of ordering, where a broader FWHM indicates a more disordered state.…”
Section: B Atomic-scale Structural Changes During β Relaxationmentioning
confidence: 99%
“…Such a trend is always observed, i.e., it is not a special properties in Pd 40 Ni 40 P 20 alloy, but is seen in metallic glasses in general. [45][46][47] To clarify the heterogeneity of the elemental concentrations quantitatively, the RMC simulation box with the length of 5.0807 nm was separated into 5 × 5 × 5 = 125 voxels, and the numbers of each element were counted. Figure 7 shows the atomic number distributions ξ i of (a) Pd, (b) Ni, (c) P, and (d) all atoms in voxels with the size of 1.0161 nm.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, application of the RMC simulations for EXAFS data analysis has been rstly reported by Gurman and McGreevy 42 and several studies have been carried out for disordered molecular and nite-size systems, 43-51 e.g., bcc-Fe, 45 undercooled Cu 46 and Ni, 47 bulk metallic glasses, 48 binary oxide glasses, 49 liquid iodine, 50 and poly-atomic molecules in gas phase. 51 In contrast, RMC is rarely applied to discrete systems composed of molecules and small clusters.…”
Section: Introductionmentioning
confidence: 99%